CPS1 augments hepatic glucagon response through CaMKII/FOXO1 pathway - Sun, Xiao-Meng; Wu, Xin; Wei, Meng-Guang; Zhu, Li-Zeng; Wu, Wen-hui; Zhou, Xin-Yue; Qi, Lian-Wen; Liu, Qun (Frontiers in Pharmacology, 2024)
Introduction: Elevated glucagon levels are a characteristic feature of type 2 diabetes. This abnormal increase in glucagon can lead to an accelerated rate of gluconeogenesis. Glucagon also stimulates hepatic metabolism of amino acids, particularly promoting the formation of urea. The specific role of carbamoyl phosphate synthetase 1 (CPS1), a rate-limiting enzyme in the urea cycle, in the development versus the persistence of glucagon-induced hyperglycemia has not been previously established. Methods: The study employed both in vivo and in vitro approaches to assess the impact of CPS1 modulation on glucagon response. CPS1 was knockdown or overexpression to evaluate its influence on hepatic gluconeogenesis. In addition, an in-silico strategy was employed to identify a potential CPS1 inhibitor. Results: Knockdown of CPS1 significantly reduced the glucagon response both in vivo and in vitro. Conversely, overexpression of CPS1 resulted in an overactive hepatic gluconeogenic response. Mechanistically, CPS1 induced the release of calcium ions from the endoplasmic reticulum, which in turn triggered the phosphorylation of CaMKII. The activation of CaMKII then facilitated the dephosphorylation and nuclear translocation of FOXO1, culminating in the enhancement of hepatic gluconeogenesis. Furthermore, cynarin, a natural CPS1 inhibitor derived from the artichoke plant, had the capacity to attenuate the hepatic glucagon response in a CPS1-dependent manner. Discussion: CPS1 played a pivotal role in mediating glucagon-induced hepatic gluconeogenesis. The discovery of cynarin as a natural inhibitor of CPS1 suggested its potential as a therapeutic agent for diabetes treatment.